2021
DOI: 10.1007/s00402-021-04088-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary stability of single-stage revision reconstruction of the anterior cruciate ligament in case of failure of dynamic intraligamentary stabilization depends on implant position during ACL repair

Abstract: Introduction The object of this study was to evaluate the primary stability of tibial interference screw (IFS) fixation in single-stage revision surgery of the anterior cruciate ligament (ACL) in the case of recurrent instability after ACL repair with dynamic intraligamentary stabilization (DIS), dependent on the implant position during DIS. Materials and methods Tibial aperture fixation in ACL reconstruction (ACL-R) was performed in a porcine knee model u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, it has been shown that primary stability of tibial graft fixation in the case of failure of ACL repair with DIS is comparable with that of aperture fixation in primary ACL reconstruction if a bone stock of 20 mm is left between the DIS implant and the tibial joint line during the initial procedure. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that primary stability of tibial graft fixation in the case of failure of ACL repair with DIS is comparable with that of aperture fixation in primary ACL reconstruction if a bone stock of 20 mm is left between the DIS implant and the tibial joint line during the initial procedure. 16 …”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that primary stability of tibial graft fixation in the case of failure of ACL repair with DIS is comparable with that of aperture fixation in primary ACL reconstruction if a bone stock of 20 mm is left between the DIS implant and the tibial joint line during the initial procedure. 16 In contrast, each ACL revision surgery in the ACL reconstruction group consisted of staged revision because of tibial tunnel widening .10 mm according to our revision standard. 41 However, when assuming a threshold of 15 mm, all the revision procedures would have been single-staged.…”
Section: Discussionmentioning
confidence: 99%
“…However, to successfully perform a revision after failed DIS, care should be taken with primary implantation. Glasbrenner et al showed that, in a porcine knee model, when a bone bridge of about 20 mm is left between the monoblock and tibial joint line knee stability of a single stage revision is comparable to that of a primary ACL reconstruction [ 32 ].…”
Section: Discussionmentioning
confidence: 99%